Transparency effects on capital flow, economic growth and income inequality - Chia, Poh San (2019)
This thesis aims to investigate the effect of transparency on capital flows, economic growth and income inequality. The first objective is to analyse the overall development in transparency and capital flows to developing countries which are motivated by the fact that the primary concern of Lucas Paradox’s is why international capital is flowing less to developing countries. The second objective is to examine whether the countries with natural resource endowment can generate a higher economic growth by taking into account the aggregate transparency and sub-aggregate transparency namely, information transparency and accountability transparency using the analysis of cross-section countries. Thirdly, the study evaluates the interrelationship among economic growth, income inequality and transparency in developing countries. The first objective uses two datasets from (i) the Global Index of Information Transparency and Accountability and (ii) the International Finance Institutes (IIF). The methods applied are panel heterogeneity estimators, namely the Common Correlation Effect Mean Group (CCEMG) and the Augmented Mean Group (AMG) which are used to examine the effect of transparency on the types of capital flows to developing countries. The number of developing countries totalled 28 countries over the period 1991 -2010. Several important findings are revealed from the study. Firstly, FDI has a weak relationship with transparency in developing countries. However, the portfolio investment has a positive and statistical significance with transparency and accountability transparency. Bank lending has a weak relation with accountability transparency, while the official flow is positively significant with information transparency. However, the inclusion of the interaction term between GDP per capita with transparency, the information transparency and accountability transparency, and the empirical result revealed that transparency is the determinant of portfolio investment and official flow, while information transparency and accountability are determinants of FDI. Thus, the empirical findings demonstrated that transparency can resolve the Lucas paradox issue that only developing countries can have a higher transparency leading to a higher capital flow. The second objective is motivated by the lack of systematic studies on the role of transparency on economic growth in natural resource endowment countries based on the system generalised method of moments (GMM) estimation. The sampling countries consisted of 73 countries over the period from 2006 to 2010. The empirical results showed that aggregate transparency and sub-aggregate, information transparency negatively affected the economic growth in natural resource countries. The sampling countries are further divided into two types of resources, point (fuel export) and diffuse (food export) resources. The empirical results revealed that fuel export is negatively associated with economic growth, while food export countries are positively associated with economic growth. The inclusion of the interaction term into analysis, interaction terms between transparency and accountability with natural resource rents are positively significant determinants of GDP per capita. Furthermore, all the interaction terms with fuel export is a positive significant determinant of GDP per capita, while the interaction terms with food export are insignificant or have benign effects to economic growth in natural resource countries despite transparency improvement. The third objective, utilises the Vector Autoregressive model to identify the interrelationship among transparency, income inequality and economic growth. Transparency and accountability transparency are identified as the key drivers for economic growth. The empirical result reveals that transparency and accountability transparency are positively significant determinants of GDP per capita. This finding is supported by several previous empirical literature which stated the good macroeconomic policies and better institution. The inclusion of financial development as an additional variable into the same model specifications, transparency and financial development play a crucial role for economic growth, while economic growth and transparency are determinants of financial development. In policy implications, the transparency is an important determinant for various types of capital flow, although bank lending has responded unfavourably to transparency. Given this, the policymakers in developing countries should take into serious consideration the transparency initiatives in order to enhance capital-growth nexus and to ensure capital large effects has by far been beneficial to growth. Transparency reform initiatives that improve oil extractive industry in respect of governance and support facilitate oil rents channel to productive investment, reduce rent-seeking and corruption in public officials. Lastly, transparency could be achieved indirectly by enhancing the existing transparency reform policies that promote good governance in order to curb the inequality and redistribution resource among population. In conclusion, countries who pursue higher transparency are allowed to reap the benefits from the capital flow in host countries, transforming the resource curse to bless economic growth and reduce income inequality. Though the effect of transparency does not undergo a faster economic growth rate, but at least it will result to a stable growth.